The (in)visibility of Torajan language: A study on linguistic landscape in South Sulawesi, Indonesia - Halim, Suwarni Wijaya; Sukamto, Katharina Endriati (Universitas Syiah Kuala, 2023)
The Torajan language is the heritage language of the Torajan people, which reflects the local wisdom and identity of the people. Yet, with the popularity of Indonesian and English as the lingua franca, there is a concern for the domain, status, and vitality of the Torajan language within the society. Therefore, this study aims to study the visibility of the language. This study offers a novel approach by looking at the use of the Torajan language in the linguistic landscape in two regencies, Tana Toraja and Toraja Utara, to determine its position in the community. The research utilized a case study design, and the source of data is linguistic landscapes found along Jalan Poros RantepaoMakale which connects the two regencies. The images of linguistic landscapes were collected by viewing the Google Street View facility provided by Google Maps, and the languages in those linguistic landscapes were noted. The findings show that Indonesian and English dominate the linguistic landscape in Tana Toraja and Toraja Utara, and the Torajan language is minimally represented in the public space of these two regencies. The lack of visibility of the language in the public space might be caused by the restricted use of the language for familial talks at home and oral indigenous rituals. However, the Torajan language needs to be used more frequently in public spaces since it could promote a positive attitude of the people, which would in turn solidify the position of the language in the society.